Role of Propolis on Tyrosine Hydroxylase Activity and Blood Pressure in Nitric Oxide Synthase-Inhibited Hypertensive Rats - Gogebakan, Ayse; Talas, Zeliha Selamoglu; Ozdemir, Ilknur; Sahna, Engin (Taylor & Francis Inc, 2012)
Reduction in the synthesis or bioavailability of nitric oxide plays a significant role in the development of hypertension. Propolis is a resinous product collected by honeybees from various plant sources. Tyrosine hydroxylase (TH) is the rate-limiting enzyme in the biosynthesis of catecholamines. The aim of this study was to examine the effect of propolis on blood pressure (BP), TH, and total RNA levels in the adrenal medulla, heart, and hypothalamus tissues in chronic nitric oxide synthase (NOS)-inhibited rats by N-w-nitro-L-arginine methyl ester (L-NAME). Rats received NOS inhibitor (L-NAME) for 15 days to produce hypertension and propolis for the last 5 days. TH activity and total RNA levels significantly increased in adrenal medulla, heart, and hypothalamus tissues in L-NAME-treated groups (P < .05). TH activity and total RNA levels of L-NAME+propolis-treated rats reduced (P < .05) compared with L-NAME-treated groups. TH activity in propolis-treated rats was reduced to the control values. L-NAME led to a significant increase in BP compared with the control group. Propolis administration to L-NAME-treated rats reduced BP but this was not statistically significant compared to L-NAME-treated groups. These results suggest that propolis decreases TH activity in NOS-inhibited hypertensive rats and thereby may modulate the synthesis of catecholamine and BP.
Keywords: tyrosine hydroxylase; L-NAME; nitric oxide; blood pressure; propolis; rat